Disparities in Judges’ Decisions on Defamation Crimes via Social Media (A Study of Medan District Court Decisions Number 2040/PID.Sus/2022/PN.Mdn and Number 3563/PID.Sus/2019/PN.Mdn) - Saragih, Fitrah Anata; Trisna, Wessy; Tarigan, Vita Cita Emia (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2025)
This study discusses the disparity of judges' decisions regarding criminal acts of defamation through social media (Study of Medan District Court Decision Number 2010 / Pid.Sus / 2022 / PN.MDN, and Medan District Court Decision Number 3563 / Pid.Sus / 2019 / PN.MDN. This study uses a normative legal research type. The results of this study are that the legal regulation of this criminal act of defamation is regulated by Law Number 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning ITE, which is contained in Article 27 paragraph 3 which reads: Every person intentionally and without the right to distribute and / or transmit and / or make accessible Electronic Information and / or Electronic Documents that contain insults and / or defamation. ". As for the two decisions above, there are differences in the judge's decisions where in the first decision the perpetrator of the criminal act of defamation committed through social media is subject to criminal sanctions in accordance with the ITE Law where the perpetrator is subject to a prison sentence of 3 month while the verdict of the two perpetrators of the crime of defamation through social media also but the judge said the verdict was acquitted where the reason the defendant committed his act was because the victim had no intention of paying the debt to the defendant and the victim also cut off communication with the defendant so that the defendant was forced to do his act, and the judge took into consideration in this case that no party was harmed and that comprehensive justice was created.